Nanogenerators integrated self-powered multi-functional wings for biomimetic micro flying robots. (October 2022) - Zheng, Hao; Li, Liangyuan; Haider, Muhammad Husnain; Wen, Dan-Liang; Zhi, Pengpeng; Tu, Cheng; Ma, Xingguang; Xu, Jing; Wang, Zhonglai; Zhang, Xiaosheng
Abstract: Under rigorous weight and power constraints, improving the energy systems and the onboard sensing approaches for flapping-wing micro air vehicles (FWMAVs) are monumental challenges. Mechanical energy transformation and integrated self-powered sensing hold great promising features to improve the flying performance of FWMAVs. Herein, we introduce novel triboelectric nanogenerators (TENGs) integrated multi-functional wings to address these challenges. Synthetically, The TENGs integrated wings can realize the mechanical energy transformation, the motion monitoring of flapping wings, and the pneumatic functions for FWMAVs. Firstly, a lightweight and ultra-thin sandwich structure integration technique with silk-fibroin film as the coated friction layer is realized for the TENGs integrated wings. Secondly, the wind tunnel test verifies the feasibility of the mechanical transformation and reveals the effects of the operating conditions of the FWMAVs on the triboelectric energy performance. The triboelectric energy performance of the TENGs integrated wings, whose entire thickness and the weight increases are less than 20 µm and 0.2 g respectively is verified to achieve 468.7 V voltage, 100.6 μA current, and 379.8 μW power. Likewise, as an attractive potential application, it is demonstrated to provide an accurate self-powered measurement of the flapping mechanism frequency based on the triboelectric principle. The aerodynamic measurements verify that the TENGs integrated wings maintain the pneumatic functions, which guarantee flight stability, and they positively enhance 29.89% of the onboard load of the FWMAV. Graphical Abstract: ga1 Highlights: An ultra-thin and flexible TENGs integration technique for wings of FWMAVs is achieved. The TENGs integrated wings provide functions of mechanical energy transformation and potential self-energy harvesting for FWMAVs. A self-powered motion monitoring for FWMAVs' flapping mechanisms is achieved. The TENGs-integrated wings are verified a positive pneumatic enhancement for FWMAVs.